2019
DOI: 10.3906/sag-1901-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of intradiscal hydrogel administiration (Gelstixtm) in lumbar degenerative discus disease

Abstract: Background/aim Degenerative disc disease (DDD) is one of the main causes of lower back pain. In this study, we evaluate the efficacy of percutaneous intradiscal GelStix administration in patients with discogenic pain due to lumbar DDD who were unresponsive to conservative methods. Materials and methods A total of 29 patients were included in the study, which took place between 2013 and 2017. Sedation was performed in the prone position in the operating room, and a C-arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“… 92 For example, GelStix Nucleus Augmentation Device is a modified polyacrylonitrile hydrogel that reconstructs the disc function by increasing hydration and IVD height. Ceylan et al 103 implanted GelStix in 29 patients with IDD and found that the VAS scores were decreased from 7.14 to 2.48 and the ODI scores were decreased from 28.14 to 17.35 after 12 months following treatment. Moreover, another randomized, double‐blind, placebo‐controlled, multicentre study has been conducted to evaluate the efficacy of treatment with the GelStix device in patients with chronic discogenic LBP, which is expected to conclude in August 2021.…”
Section: Hydrogel‐based Biomaterialsmentioning
confidence: 99%
“… 92 For example, GelStix Nucleus Augmentation Device is a modified polyacrylonitrile hydrogel that reconstructs the disc function by increasing hydration and IVD height. Ceylan et al 103 implanted GelStix in 29 patients with IDD and found that the VAS scores were decreased from 7.14 to 2.48 and the ODI scores were decreased from 28.14 to 17.35 after 12 months following treatment. Moreover, another randomized, double‐blind, placebo‐controlled, multicentre study has been conducted to evaluate the efficacy of treatment with the GelStix device in patients with chronic discogenic LBP, which is expected to conclude in August 2021.…”
Section: Hydrogel‐based Biomaterialsmentioning
confidence: 99%